SCALE UP DAN PENGEMBANGAN SISTEM KONTROL EXPERT BIOFERMENTOR BIJI KOPI - A. Musawwirul Munir Syasmar; Abdul Waris; Mahmud Achmad (Rang Teknik Journal, 2024)
Coffee bean fermentation is one of a series of post-harvest processes that can affect the quality of coffee. A biofermenter with a capacity of 1 kg has been made and researched and the results are able to provide good quality to the fermented coffee beans. To produce a larger biofermenter, it is necessary to carry out research on scaling up the biofermenter to a capacity of 5 kg. This research aims to produce a coffee bean biofermenter with a capacity of 5 kg equipped with an expert control system with the same or better performance than a biofermenter with a capacity of 1 kg. The research method used was design, starting from designing the fermentation space and container, electrical energy requirements, control system and software , and testing the performance of the biofermenter by fermenting 5 kg of coffee beans within 12 hours and repeated twice. Next, data analysis was carried out which included testing the pH of the fermentation solution, pulp content, water content, color of coffee beans, pH of coffee grounds and total acidity of coffee grounds. The research results show that the biofermenter can work well, characterized by no overshoot , small steady state error in the range of 2-5% . and a short time setting of 80 minutes, stable temperature around the setting point (SP) 40°C. In testing the quality of the fermentation results using a coffee bean biofermenter, it showed that the pH of the fermentation solution was 5.56, the pulp released was 14.54%, almost the same as the research before the scale up , namely the pulp released was 13.3%, the water content was 11.7%, the color of the coffee beans before scale up notation L* 31.63 and after scale up L* 31.71, pH of coffee grounds before scale up 5.7 and after scale up 4.93, total acid titrated before scale up 0.23% and after scaling up 1.73%.Keywords: Coffee Bean Biofermenter, Expert , Control System, Infrared, Electrical Power